Respiratory Syncytial Virus and Rhinovirus Bronchiolitis Are Associated With Distinct Metabolic Pathways - Stewart, Christopher J (J Infect Dis, 2018)
BACKGROUND: Bronchiolitis, the leading cause of hospitalization among infants in the United States, is most commonly caused by respiratory syncytial virus (RSV), followed by rhinovirus (RV). Conventional perception is that bronchiolitis is a single entity, albeit with different viral etiologies and degrees of severity. METHODS: We conducted a cross-sectional study of nasopharyngeal aspirates from 106 infants hospitalized with bronchiolitis due to either RSV only (80 patients) or RV only (26 patients). We performed metabolomics analysis and 16S ribosomal RNA gene sequencing on all samples and metagenomic sequencing on 58 of 106 samples. RESULTS: Infants with RSV-only and RV-only infections had significantly different nasopharyngeal metabolome profiles (P < .001) and bacterial metagenome profiles (P < .05). RSV-only infection was associated with metabolites from a range of pathways and with a microbiome dominated by Streptococcus pneumoniae. By contrast, RV-only infection was associated with increased levels of essential and nonessential N-acetyl amino acids and with a high relative abundance of Haemophilus influenzae. These co-occurring species were associated with driving the bacterially derived metabolic pathways. Multi-omic analysis showed that both the virus and the microbiome were significantly associated with metabolic function in infants hospitalized with bronchiolitis. CONCLUSION: Although replication of these findings is necessary, they highlight that bronchiolitis is not a uniform disease between RSV and RV infections, a result with future implications for prevention and treatment.